2022
DOI: 10.7150/jca.67990
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-199a-5p/SLC2A1 axis regulates glucose metabolism in non-small cell lung cancer

Abstract: Lung cancer is acknowledged as a common cancer with high morbidity and mortality. MicroRNAs (miRNAs), kind of non-coding single-stranded RNA molecules, can be used in cancer clinical treatments. In this research, miR-199a-5p was seen lowly expressed in NSCLC sera samples. miR-199a-5p suppressed the cell proliferation, migration and arrested cell cycle in NSCLC cell lines. The results showed that SLC2A1 (glucose transporter 1, GLUT1) was a direct target of miR-199a-5p. Downregulation of SLC2A1 could not only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…In our previous study, Xu et al [ 66 ] found that SLC2A1, a member of the GLUTs, was a direct target of miR-199a-5p. Down-regulation of SLC2A1 suppressed NSCLC cell proliferation, consistent with the role of miR-199a-5p.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, Xu et al [ 66 ] found that SLC2A1, a member of the GLUTs, was a direct target of miR-199a-5p. Down-regulation of SLC2A1 suppressed NSCLC cell proliferation, consistent with the role of miR-199a-5p.…”
Section: Resultsmentioning
confidence: 99%
“…SLC2A1 encodes a glucose transporter protein, GLUT1, which plays a key role in the uptake of glucose by cells, transporting glucose from outside the cell to the inside, thereby providing raw materials for glycolysis ( Liu et al, 2022 ). The study by Xu Y. et al (2022) suggests that miRNA-199a-5p promotes the malignant progression of non-small cell lung cancer by targeting SLC2A1. SLCO4C1 encodes a member of the Organic Anion Transporting Polypeptides (OATPs) family, primarily expressed on the basolateral side of renal tubular epithelial cells, responsible for transporting substances from the cell into the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of SLC2A1 can interfere with glycolysis in lung cancer cells. Thus, it can inhibit cell proliferation, migration, and the cell cycle and promote apoptosis ( 58 , 59 ). In addition, for the intersected genes of two features, tumor-secreted adrenomedullin ( ADM ) is recognized as a type of regulatory polypeptide driving both tumor and lymph node angiogenesis.…”
Section: Discussionmentioning
confidence: 99%